Analyzing student inquiry in online and offline classes during the Covid-19 pandemic through momentum and impulse worksheets - Baihaqi, Habibah Khusna; Jumadi, Jumadi; Mardiani, Annisaa’; Religia, Racy (Momentum: Physics Education Journal, 2021)
During the Covid-19 pandemic, it is necessary to develop an effective physics learning media used in a short learning time. This study aims to develop a package of worksheets based on an inquiry learning model that is integrated with traditional games. This research is a research and development using 4D model which is carried out at the define, design and develop stages. Validation was carried out by 3 experts and the worksheets were tested on 45 students of class X consisting of online and offline classes. The results of the development show that the momentum practicum worksheet is 3.68 in the valid range, the law of conservation momentum practicum worksheet is 3.66 in the valid and very good range, the coefficient of restitution and type of collision practicum worksheets are 3.74 and 3.73 in the valid and very good range, also the worksheet package scored 3.67 which means valid and very good. The implementation of learning is 98.21% and the readability questionnaire shows that 82.27% of students agree that the worksheet developed is very interesting and easy to use. The achievement of the inquiry process in the online class is 86.10 while in the offline class is 93.84. The results show that this worksheet is effective in optimizing the inquiry process both online and offline so that it can be used to investigate the topic of momentum and impulse by class X science students during the Covid-19 pandemic.